2014
DOI: 10.1089/ten.tea.2013.0151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Uncultured Marrow Mononuclear Cells and Culture-Expanded Mesenchymal Stem Cells in 3D Collagen-Chitosan Microbeads for Orthopedic Tissue Engineering

Abstract: Stem cell-based therapies have shown promise in enhancing repair of bone and cartilage. Marrow-derived mesenchymal stem cells (MSC) are typically expanded in vitro to increase cell number, but this process is lengthy, costly, and there is a risk of contamination and altered cellular properties. Potential advantages of using fresh uncultured bone marrow mononuclear cells (BMMC) include heterotypic cell and paracrine interactions between MSC and other marrow-derived cells including hematopoietic, endothelial, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 88 publications
(115 reference statements)
4
55
0
1
Order By: Relevance
“…113 Recently, a chitosan-collagen hydrogel microbead was reported as a vehicle for culture and delivery of cultured-expanded mesenchymal stem cells or fresh bone marrow mononuclear cells. 117 The microbeads were fabricated via a two-step process. Chitosan, collagen and β-glycerophosphate were mixed in solution and bead formation was achieved using a water-in-oil emulsion system followed by thermally induced gelation at physiological temperature.…”
Section: Advances In Chitosan-based Scaffolds For Bone Tissue Engimentioning
confidence: 99%
“…113 Recently, a chitosan-collagen hydrogel microbead was reported as a vehicle for culture and delivery of cultured-expanded mesenchymal stem cells or fresh bone marrow mononuclear cells. 117 The microbeads were fabricated via a two-step process. Chitosan, collagen and β-glycerophosphate were mixed in solution and bead formation was achieved using a water-in-oil emulsion system followed by thermally induced gelation at physiological temperature.…”
Section: Advances In Chitosan-based Scaffolds For Bone Tissue Engimentioning
confidence: 99%
“…19,20 Cell collections containing bone marrow-derived mononucleated cells (BMNCs)-a small fraction of which are BMSCs-are seeded within biomaterials for 3D isolation, expansion, and subsequent differentiation. 20,21 Cell seeding density is a transplantation variable that has not been evaluated in detail to date for either 2D-or 3D-expanded BMSCs. Healthy articular cartilage naturally contains 9.6 × 10 6 chondrocytes/cm 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A two-paddle impeller stirred the mixture at 700 rpm for 6 min at 37 °C and then for 30 min on ice to gel the resulting microbeads. Previous work has shown that use of FBS acts as a surfactant that facilitates the separation of the beads from the oil phase during production, and also aids in maintaining high cell viability [17, 21]. …”
Section: Methodsmentioning
confidence: 99%